2002
DOI: 10.1103/physrevlett.89.128301
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically Locked-In Colloidal Transport in an Array of Optical Tweezers

Abstract: We describe measurements of colloidal transport through arrays of micrometer-scale potential wells created with holographic optical tweezers. Varying the orientation of the trap array relative to the external driving force results in a hierarchy of lock-in transitions analogous to symmetry-selecting processes in a wide variety of systems. Focusing on colloid as a model system provides the first opportunity to observe the microscopic mechanisms of kinetic lock-in transitions and reveals a new class of statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
350
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(369 citation statements)
references
References 19 publications
14
350
0
Order By: Relevance
“…The deflection angle between the flux and the direction of F depends on the commensurability between the particle trajectories and the underlying periodic potential. This effect has been used for particle sorting [52][53][54]. Recent studies also showed that the multidimensional nonequilibrium steadystate distribution determines the ratio between the transport coefficients along different primitive crystal directions [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…The deflection angle between the flux and the direction of F depends on the commensurability between the particle trajectories and the underlying periodic potential. This effect has been used for particle sorting [52][53][54]. Recent studies also showed that the multidimensional nonequilibrium steadystate distribution determines the ratio between the transport coefficients along different primitive crystal directions [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…The direction of motion of the locked particles undergoes a series of steps as a func-tion of the effective angle of drive with respect to the substrate. The steps are centered at integer and rational ratios of the angle of drive and form a devil's staircase structure [46][47][48]50,51,53,54 . In the skyrmion system, we observe directional locking effects when the direction of external drive is fixed with respect to the substrate and the drive amplitude is varied.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments and computational studies have shown that in the absence of a drive, a variety of orderings can arise for colloidal particles interacting with one-dimensional (1D) periodic substrates [13,32,33], two-dimensional (2D) periodic substrates [15,20,21,[34][35][36][37][38], 2D quasiperiodic substrates [39][40][41][42][43], or 2D random substrates [44]. While these studies have provided a better understanding of several features of commensurateincommensurate behaviors, being able to dynamically control the particle ordering and dynamics could lead to a variety of applications, including self-assembled structures, particle separation, and photonic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Periodic pinning arrangements of this type have been experimentally realized in colloidal systems and studied in the range f = 4.0 to f = 5.5, with a triangular colloidal lattice observed at f = 4.0 when the pinning strength was such that each pinning site captures only one particle [48]. Such pinning arrays have also been used to study dynamical locking for colloidal particles driven over a substrate at different angles with respect to the substrate symmetry directions [34]. Experimental and numerical studies of vortex systems using similar 2D periodic pinning arrays also obtained a triangular vortex lattice at f = 4.0 and a square lattice at f = 5.0 [5,7] with domain wall and stripe states between these fillings [5].…”
Section: Introductionmentioning
confidence: 99%